2019
DOI: 10.1016/j.jaad.2018.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the dermatology residency match from 2007 to 2018: Implications for the dermatology workforce

Abstract: AOA, Alpha Omega Alpha; CK, clinical knowledge; pp, percentage point; USMLE, United States Medical Licensing Examination. *Only specialties with 50 or more positions are included. y Transitional year residency applicants are included only in these years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The relatively low median h-index may reflect an applicant's limited research experience, as medical students may be more likely to publish in lower impact journals and possess short research careers. Our study found that matched dermatology candidates hold increasing research accomplishments each year, which is consistent with trends seen in the literature [2][3][13][14]. The rising h-index of successful candidates may indicate that not only quantity but the quality of publications is increasing.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The relatively low median h-index may reflect an applicant's limited research experience, as medical students may be more likely to publish in lower impact journals and possess short research careers. Our study found that matched dermatology candidates hold increasing research accomplishments each year, which is consistent with trends seen in the literature [2][3][13][14]. The rising h-index of successful candidates may indicate that not only quantity but the quality of publications is increasing.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the expansion in the number of dermatology residency programs, the proportion of candidates failing to match in dermatology remains substantial [1][2], and it is becoming increasingly difficult to match into a dermatology residency position [3]. Multiple quantifiable factors play a role in candidate success, such as the United States Medical Licensing Examination (USMLE) scores, research productivity, and Alpha Omega Alpha (AOA) membership [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatology is well positioned to leverage DL to improve patient care, with its emphasis on visual analysis. Given the shortage of dermatologists in the U.S. (Jayakumar and Lipoff, 2019) and the increasing incidence of cutaneous melanoma (National Cancer Institute, 2020), AI may play an increasingly important role in improving access to and quality of dermatological care. This review summarizes research on the automated classification and monitoring of skin lesions, discusses barriers to clinical adoption, and proposes metrics for AI model performance.…”
Section: Introductionmentioning
confidence: 99%